TETRAHEDRAL COMPLEX OF Cr3+ AND Cr4+ IONS IN Bi12SiO20 - Petkova, Petya (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Absorption measurement is taken in the visible spectral region (650 – 1300 nm). The dopants Cr3+ and Cr4+ ions occupy the tetrahedral sites in the crystal lattice of doped sillenite. The energy level structure of these ions in Bi12SiO20:Cr (BSO:Cr) are presented. The Dq-, B- and C-parameters of the crystal field theory for the Cr3+ and Cr4+ ions were obtained. The spin-coupling energy is also calculated for the chromium ions.